MyoD-induced expression of p21 inhibits cyclin-dependent kinase activity upon myocyte terminal differentiation. - Guo, K (1995)
The terminal differentiation of C2C12 skeletal muscle cells involves the activation of unique sets of genes and an irreversible withdrawal from the cell cycle. This process is associated with a decrease in cdk2 activity in cell extracts. The decrease in cdk2 activity correlates with diminished levels of cdk2 and cyclin A and with a marked induction of the p21 cyclin-dependent kinase (cdk) inhibitor. The upregulation of p21 occurred at the levels of mRNA and protein, and p21 formed a complex with the cyclin kinases in myotubes. Further, the immunodepletion of p21 from myotube extracts neutralized the heat-stable cdk2 inhibitory activity that was induced upon myogenic differentiation. The levels of p21 mRNA, protein, and activity remained constant in myotubes when they were reexposed to mitogen-rich growth medium, indicating that permanent changes in the cell's genetic program contribute to its sustained expression following terminal differentiation. Indeed, 10T1/2 fibroblasts transformed with the myogenic factor MyoD, but not the parental multipotent cells, upregulated p21 transcript levels when induced to differentiate by serum withdrawal, demonstrating that the upregulation is an integral feature of myogenic commitment and differentiation. The functional consequences of this upregulation were indicated by ectopically expressing p21 in myoblasts; this was sufficient for cell cycle arrest in mitogen-rich growth medium. The induction and sustained expression of p21 appears to be a contributory mechanism by which myocytes irreversibly exit the cell cycle upon terminal differentiation.